2007
DOI: 10.1152/ajpregu.00827.2006
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in conducted vasodilation: effects of exercise training and role in functional hyperemia

Abstract: Bearden SE, Linn E, Ashley BS, Looft-Wilson RC. Age-related changes in conducted vasodilation: effects of exercise training and role in functional hyperemia. Am J Physiol Regul Integr Comp Physiol 293: R1717-R1721, 2007. First published July 25, 2007; doi:10.1152/ajpregu.00827.2006.-Conducted vasodilation may coordinate blood flow in microvascular networks during skeletal muscle contraction. We tested the hypotheses that 1) exercise training enhances conducted vasodilation and 2) age-related changes in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The RT-PCR results showed that no significant differences in the Cx43 mRNA levels were found between the groups, as supported by the in situ hybridization detection. Obvious decreased expression of Cx43 mRNA was found in trained mice during acute exercise [20,35] , while chronic exercise training has no effect on the expression of Cx43 mRNA in intact blood vessels in vivo [36] . Therefore, we speculated that different exercise intensity has different effects on the expression of Cx43 mRNA.…”
Section: Discussionmentioning
confidence: 92%
“…The RT-PCR results showed that no significant differences in the Cx43 mRNA levels were found between the groups, as supported by the in situ hybridization detection. Obvious decreased expression of Cx43 mRNA was found in trained mice during acute exercise [20,35] , while chronic exercise training has no effect on the expression of Cx43 mRNA in intact blood vessels in vivo [36] . Therefore, we speculated that different exercise intensity has different effects on the expression of Cx43 mRNA.…”
Section: Discussionmentioning
confidence: 92%
“…Although Western blot and immunohistological analysis did not demonstrate significant right–left differences in Cx40 protein expression in the Cx40 +/+ mice, quantification of Cx40 mRNA expression found chamber-specific differences that followed a similar pattern to the CV findings. It is recognized that qRT-PCR is an assay that is less variable than Western blot 28. Heterogeneity in Cx40 mRNA expression (LAA>RAA) was detected in Cx40 +/+ mice and lost with partial deletion of Cx40, mirroring CV findings.…”
Section: Discussionmentioning
confidence: 93%
“…To furnish evidence for this scenario our functional experiments show that after the SK Ca /IK Ca channels (known mediators of EDHF and hyperpolarization spread) (2) were inhibited or in the presence of 30 mM K ϩ solution (known to inhibit EDHF response), the conducted coronary dilation to bradykinin is abolished. Given that previous studies found an impaired conducted vasodilation in the skeletal muscle of rodent models of aging (1,2), in this study we also determined whether the conducted dilation is altered in coronary resistance arteries of older patients. We found a significant reduction in conducted dilation to bradykinin in older (Ն64 yr) patients compared with younger individuals (Ͻ64 yr).…”
Section: Discussionmentioning
confidence: 98%
“…Behringer et al (2) have shown that aging impairs electrical conduction along endothelial cell tubes obtained from resistance arteries of the 24-to 26-mo-old mice. In old (19 to 20 mo) mice, Bearden et al (1) found that conducted vasodilation is reduced in the skeletal muscle microcirculation, in vivo, compared with younger (12-14 mo) mice. These data indicate that aging impairs conducted vasodilation in the skeletal muscle circulation and demonstrate a key role in dysfunctional microvascular endothelium in this process.…”
mentioning
confidence: 99%